Representasi Kepatuhan Pajak dalam Pamflet Lapor SPT Tahunan Direktorat Jenderal Pajak: Kajian Semiotika terhadap Konstruksi Tax Compliance - Sri Mulyani Latjompo; Sri Nurul Izzah, Namra Namra , Darwis Said; Nadhirah Nagu (STIE AMKOP, 2026)
This study aims to analyze the representation of tax compliance in Annual Tax Return (SPT) reporting pamphlets published by the Directorate General of Taxes (DGT). The research employs a qualitative approach using Roland Barthes’ semiotic method through denotative, connotative, and mythological analyses. The objects of the study consist of three official DGT pamphlets related to Annual Tax Return reporting through Coretax and M-Pajak. Data were collected through documentation and literature review. The findings indicate that the visual and verbal signs in the pamphlets not only convey tax-related information but also represent tax compliance as a simple, modern, and everyday practice. At the mythological level, the pamphlets construct the ideal taxpayer as a responsible, technologically adaptive, and digitally compliant citizen. These findings suggest that DGT pamphlets function as a communication medium that shapes public awareness and social identity regarding the importance of tax compliance in the digital era. Kata kunci: kepatuhan pajak, tax compliance, semiotika Roland Barthes, Direktorat Jenderal Pajak, Coretax.